Experimental Free-Space Distribution of Entangled Photon Pairs over a Noisy Ground Atmosphere of 13km - Peng, C; Yang, T; Bao, X; Jun-Zhang; Jin, X; Feng, F; Yang, B; Yang, J; Yin, J; Zhang, Q; Li, N; Tian, B; et al. (2004)
We report free-space distribution of entangled photon pairs over a noisy ground atmosphere of 13km. It is shown that the desired entanglement can still survive after the two entangled photons have passed through the noisy ground atmosphere. This is confirmed by observing a space-like separated violation of Bell inequality of $2.45 ± 0.09$. On this basis, we exploit the distributed entangled photon source to demonstrate the BB84 quantum cryptography scheme. The distribution distance of entangled photon pairs achieved in the experiment is for the first time well beyond the effective thickness of the aerosphere, hence presenting a significant step towards satellite-based global quantum communication.